Learning Analytics pada Hubungan antara Pendidikan Orang Tua dan Hasil Belajar Peserta Didik SMA pada Mata Pelajaran Fisika di Indonesia - Dendodi Dendodi; Haratua Tiur Maria S; Venny Karolina (Departement of Mathematics Education, 2023)
Family factors are the most important aspect in the development of student learning outcomes, especially regarding the educational background of the student's parents. The issue of parental educational background is often related to student learning outcomes at school. The aim of this research is to determine the relationship between parental education and student learning outcomes. This research uses experimental research analysis methods. Experimental research analysis is a research method whose aim is to find the influence between two variables (dependent and independent). The test used in this research method is the Pearson correlation (product moment) test. Data collection instruments were through mid-semester assessments for learning outcomes and through questionnaires for parent education data with a sample size of 14 people. Based on data analysis using the Pearson correlation test, a sig value was obtained 0.004 < 0.05 which proves that there is a relationship between the educational background of students' parents and learning outcomes and has a degree of relationship of 0.722 which is categorized as a strong relationship. So from this description it can be concluded that there is a significant influence between the education of students' parents and the physics learning outcomes of class XI MIA SMAS Indonesia Muda Sungai Raya and this relationship has a strong status.